Identification of microRNA-221/222 and microRNA-323-3p association with rheumatoid arthritis via predictions using the human tumour necrosis factor transgenic mouse model. Issue 10 (5th May 2012) - Pandis, Ioannis; Ospelt, Caroline; Karagianni, Niki; Denis, Maria C; Reczko, Martin; Camps, Carme; Hatzigeorgiou, Artemis G; Ragoussis, Jiannis; Gay, Steffen; Kollias, George
Abstract : Objective: To identify novel microRNA (miR) associations in synovial fibroblasts (SF), by performing miR expression profiling on cells isolated from the human tumour necrosis factor (TNF) transgenic mouse model (TghuTNF, Tg197) and patients biopsies. Methods: miR expression in SF from TghuTNF and wild-type (WT) control mice were determined by miR deep sequencing (miR-seq) and the arthritic profile was established by pairwise comparisons. Quantitative PCR analysis was utilised for profile validation, miR and gene quantitation in patient SF. Dysregulated miR target genes and pathways were predicted via bioinformatic algorithms and validated using gain-of-function coupled with reporter assay experiments. Results: miR-seq demonstrated that TghuTNF-SF exhibit a distinct pathogenic profile with 22 significantly upregulated and 30 significantly downregulated miR. Validation assays confirmed the dysregulation of miR-223, miR-146a and miR-155 previously associated with human rheumatoid arthritis (RA) pathology, as well as that of miR-221/222 and miR-323-3p. Notably, the latter were also found significantly upregulated in patient RA SF, suggesting for the first time their association with RA pathology. Bioinformatic analysis suggested Wnt/cadherin signalling as a putative pathway target. miR-323-3p overexpression was shown to enhance Wnt pathway activation and decrease the levels of its predicted target β-transducin repeat containing, an inhibitor of β-catenin. Conclusions: Using miR-seq-based profiling in SF from the TghuTNF mouse model and validations in RA patient biopsies, the authors identified miR-221/222 and miR-323-3p as novel dysregulated miR in RA SF. Furthermore, the authors show that miR-323-3p is a positive regulator of WNT/cadherin signalling in RA SF suggesting its potential pathogenic involvement and future use as a therapeutic target in RA.